Development and psychometric testing of an instrument for measuring social participation of adolescents: study protocol of a prospective mixed-methods study. Issue 2 (24th February 2019) - Baerwalde, Tim; Gebhard, Britta; Hoffmann, Laura; Roick, Julia; Martin, Olaf; Neurath, Anna-Lena; Fink, Astrid
Abstract : Introduction: Social participation is an important part of a young person's life. It influences the social experience, social-emotional development and dimensions of competence experience. This applies to people with or without physical disabilities or chronic diseases. Currently, there is no reliable assessment tool for measuring social participation of adolescents in Germany although social participation is a central goal of rehabilitation. The aim of this study is to develop, test and pilot an instrument that assesses social participation for adolescents between the ages of 12 and 17 years and to start a psychometric test. Methods and analysis: In a sequential mixed-methods study, adolescents with and without physical disabilities or chronic diseases are asked about their experiences with social participation as well as the individual significance of self-determination through semistructured interviews. The perspective of adolescents is supplemented by focus groups that will be conducted first with experts from social paediatric care and second with legal guardians. Based on this, an assessment instrument will be developed, evaluated and implemented in exemplary social paediatric centres (SPCs) and rehabilitation clinics and psychometrically tested in a pilot study. Ethics and dissemination: The study will be conducted in accordance with the principles of the revised Helsinki Declaration. The study was approved by the Ethics Review Committee at the Martin-Luther-University Halle-Wittenberg. The developed assessment instrument can be used in science to identify disadvantaged groups and to compensate for the disadvantages that could impair development. For this purpose, the results will be presented at scientific conferences and published in international peer-reviewed journals. In practice, the instrument can be used to determine the goals of rehabilitation together with the adolescents and to evaluate the achievement of these goals. For this, implementation workshops and further training will be organised and carried out in children's rehabilitation clinics and SPCs. Trial registration number: DRKS00014739; Pre-results.